Effects of rotation on natural convection cooling from three rows of heat sources in a rectangular cavity - JIN, L; TOU, K; TSO, C (2005)
Two-dimensional unsteady numerical studies are made on an air-filled enclosure rotated about its horizontal axis with an array of three rows of heat sources on one of the walls, revealing three physically realizable phenomena, namely, uniperiodic oscillation, multi-periodic oscillation and chaotic oscillation. The evolutionary process of flow field and natural convection characteristics from stationary to rotating situation is studied. Rotation results in an imbalance between clockwise and counter-clockwise circulations, increases heat transfer in the worst scenario, reduces the oscillation of Nusselt number, and improves or reduces mean performance in each cycle. The optimal distribution of heaters in rotating fluid is close to the results in the stationary situation if they have same dominated circulation direction. (c) 2005 Elsevier Ltd. All rights reserved.